2020
DOI: 10.1039/d0cc05888b
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous-MoO3−x/MoS2 heterostructure: in situ oxidizing amorphization of S-vacancy MoS2 for enhanced alkaline hydrogen evolution

Abstract: Cost-effective and durable electrocatalysts for alkaline hydrogen evolution reaction (HER) are urgently pursued. The slow HER kinetics suppressed by water dissociation hinder the application of catalysts in alkaline media. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…As shown in the Figure 3D, the main peak occurred at binding energies of 232.88 eV for Mo 3d 5/2 and 236.08 eV for Mo 3d 3/2 ; these are typical characteristic values of the 3d orbital doublet Mo 6+ 16 . The O 1s spectrum (Figure 3E) also indicates that the surface of MoO x @PCC is composed by amorphous MoO 3 nature 25 . The XRD (Figures 1B and 3A), HRTEM (Figure 2A), and XPS (Figures 3D‐F) results reveal that the MoO x aggregates are composed of the amorphous MoO 3 matrix and tiny MoO 2 nanocrystals.…”
Section: Resultsmentioning
confidence: 73%
“…As shown in the Figure 3D, the main peak occurred at binding energies of 232.88 eV for Mo 3d 5/2 and 236.08 eV for Mo 3d 3/2 ; these are typical characteristic values of the 3d orbital doublet Mo 6+ 16 . The O 1s spectrum (Figure 3E) also indicates that the surface of MoO x @PCC is composed by amorphous MoO 3 nature 25 . The XRD (Figures 1B and 3A), HRTEM (Figure 2A), and XPS (Figures 3D‐F) results reveal that the MoO x aggregates are composed of the amorphous MoO 3 matrix and tiny MoO 2 nanocrystals.…”
Section: Resultsmentioning
confidence: 73%
“…The low value of R ct confirms that the efficient charge transfer can lead to accelerated electrocatalytic behaviour 48 . It may be expected that the WSe 2 /WO 3−X exhibits a higher interfacial electron transfer than pristine WSe 2 because of the higher Fermi level of WO 3−X 49 . Wu et al demonstrated theoretical and experimental results of enhanced water dissociation by MoS 2 ‐MoO 3−X due to modified Gibbs free energy of the adsorption of the water molecule and the intermediate OH atoms 49 .…”
Section: Resultsmentioning
confidence: 78%
“…48 It may be expected that the WSe 2 /WO 3ÀX exhibits a higher interfacial electron transfer than pristine WSe 2 because of the higher Fermi level of WO 3ÀX . 49 Wu et al demonstrated theoretical and experimental results of enhanced water dissociation by MoS 2 -MoO 3ÀX due to modified Gibbs free energy of the adsorption of the water molecule and the intermediate OH atoms. 49 p-WO 3Àx dopants in WSe 2 cause the p-p homo doping, which leads to delocalised electrons in electrocatalysts and enhances the rate of hydrogen evolution reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[125][126] Intriguingly, the recently emerged amorphous-crystalline heterostructures have been considered as laudable candidates to remarkably enhance the HER kinetics benefitting from their unique electronic interactions in hetero-phase interfaces. [112,116,119,[127][128][129][130][131] For example, Sun et al reported a pH-universal HER electrocatalyst with amorphous-crystalline heterostructure formed by amorphous rhodium hydroxide and crystalline nickel tellurium nanorods (a-Rh(OH) 3 /NiTe), which shows dramatically lowered overpotentials of 64, 109, and 51 mV at 100 mA cm −2 in acidic, neutral and alkaline solutions, respectively. [112] Shi et al prepared a hierarchical core-shell nanorod array comprising an inner crystalline CoP nanorod and an outer amorphous CoB nanosheet (CoP@a-CoB), which delivers outstanding HER properties with impressive overpotentials of 56.3 and 81.2 mV at 10 mA cm −2 in alkaline and acidic media, respectively.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%